BRANDING STRATEGY TO INCREASE HYDROPONIC MELON SALES REVENUE AT ARH FARM 2 - Ani, Rindi; Setiyani, Rahmawati; Waluyo, Sugeng Edi (LPPM Universitas Duta Bangsa Surakarta, 2025)
Branding is an important part of increasing competitiveness and business income, including in modern agricultural sectors like hydroponic watermelon farming. ARH FARM 2, as a small and medium-sized agrotourism business that picks watermelons, needs the right branding strategy to reach a wider market. This study uses a descriptive method and T-score analysis with three indicators: brand identity, promotion, and brand image, viewed from both consumer and producer perspectives. The T-score results from consumers are 14.17 (brand identity), 14.80 (promotion), and 17.14 (brand image), while from producers they are 16.04, 12.00, and 18.20. These results show that strengthening brand image and brand identity should be a priority, while promotion needs to be improved. The right branding strategy is expected to help ARH FARM 2 increase its income sustainably.